Computational Screening of Bioactive Compounds from Aglaia odorata L. Leaves as Potential Inhibitors of Matrix Metalloproteinase-1 for Premature Skin Aging - Khoirista Noor Rohmah; Ilham Kurniawan; Febby Yulia Hastika; Dina Ayuning Tyas (Universitas Pahlawan Tuanku Tambusai, 2026)
Premature skin aging is driven by UV‑induced upregulation of matrix metalloproteinase‑1 (MMP‑1), which degrades dermal collagens. Natural products are explored as safer anti‑aging alternatives. This study computationally screened five bioactive compounds from Aglaia odorata leaves (β‑turmerone, phytol, methyl cinnamate, n‑hexadecanoic acid, methyl palmitate) against MMP‑1 (PDB ID: 1HFC) and predicted their drug‑likeness, skin permeability, and safety for topical use. Molecular docking was performed using AutoDock Vina; ADMET properties were predicted with SwissADME and pkCSM. All compounds complied with Lipinski’s Rule of Five (zero violations). Methyl cinnamate formed three hydrogen bonds including with the catalytic residue Glu219. β‑Turmerone showed the highest affinity (ΔG = –6.5 kcal/mol, Ki = 17.0 µM). Phytol, methyl palmitate, and n‑hexadecanoic acid exhibited weaker binding (Ki = 33.5–78.0 µM), while the positive control PLH had ΔG = –7.5 kcal/mol (Ki = 3.14 µM). ADMET predictions showed excellent skin permeability for phytol and the fatty acid derivatives (Log Kp > –3.0 cm/h). All compounds were non‑mutagenic, non‑hepatotoxic, and safe for skin sensitisation. Methyl cinnamate and β‑turmerone are the most promising A. odorata‑derived MMP‑1 inhibitors, supporting further validation as natural anti‑aging cosmeceuticals.